2018
DOI: 10.1073/pnas.1711516115
|View full text |Cite
|
Sign up to set email alerts
|

Germ-layer commitment and axis formation in sea anemone embryonic cell aggregates

Abstract: SignificanceEmbryonic development of any animal species is a robust series of morphogenetic events tightly controlled by molecular signals. However, the variety of developmental trajectories undertaken by different members of the same phylum suggests that normal development in each particular species might involve only a subset of morphogenetic capacities available to the highly developmentally plastic embryonic cells. Here we show that, faced by a new developmental context, the aggregates of dissociated gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
(58 reference statements)
2
46
0
Order By: Relevance
“…In contrast, presumptive endomesodermal cells derived from an injected blastomere develop into a normal endomesodermal epithelium (Figure 3F). Our results compliment the work of (Kirillova et al, 2018) and demonstrate that the proper cell-cell adhesion of the ectodermal layer somehow regulates trans-epithelially the integrity of the endomesodermal layer. This regulation may maintain the tension between cells during invagination at gastrula stages, or, in conjunction with the extracellular matrix (ECM) and basal cues, it may influence signaling patterns necessary to organize epithelial layers during N. vectensis embryogenesis.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, presumptive endomesodermal cells derived from an injected blastomere develop into a normal endomesodermal epithelium (Figure 3F). Our results compliment the work of (Kirillova et al, 2018) and demonstrate that the proper cell-cell adhesion of the ectodermal layer somehow regulates trans-epithelially the integrity of the endomesodermal layer. This regulation may maintain the tension between cells during invagination at gastrula stages, or, in conjunction with the extracellular matrix (ECM) and basal cues, it may influence signaling patterns necessary to organize epithelial layers during N. vectensis embryogenesis.…”
Section: Resultssupporting
confidence: 90%
“…9H,I). We have previously reported that the two epithelial layers (ectoderm and endoderm) are formed 24 h after re-aggregation (Kirillova et al, 2018). Both cell layers possessed basal and apical cadherin cell junctions (Fig.…”
Section: Function Of Classical Cadherins In Early Developmentmentioning
confidence: 83%
“…Therefore, to assess the function of Cdh3 in establishing new cell junctions we used an aggregate assay. Nematostella gastrulae can be dissociated into single cells and small clusters and can be re-aggregated by centrifugation into cell aggregates (Kirillova et al, 2018). We followed the establishment of cell contacts and the formation of the epithelium in developing cell aggregates (Fig.…”
Section: Function Of Classical Cadherins In Early Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to assess the function of Cdh3 in establishing new cell junctions we used an aggregate assay. Nematostella gastrulae can be dissociated into single cells and small clusters and can be re-aggregated by centrifugation into the cell aggregates (Kirillova et al, 2018). We followed the establishment of cell contacts and the formation of the epithelium in the developing cell aggregates (Fig.…”
Section: Function Of Classical Cadherins In Early Developmentmentioning
confidence: 99%